International Legal Problems of Cooperation in the Detection, Investigation and Prevention of Crimes Committed Using Information and Telecommunication Networks and in the Field of Computer Information - E. A. Arkhipova; V. N. Dodonov (Московский журнал международного права, 2020)
INTRODUCTION. Based on the analysis of international acts, as well as the practice of their application, the authors consider the international legal problems of interaction in the detection, investigation and prevention of crimes committed using information and telecommunication networks and in the field of computer information.MATERIALS AND METHODS. The materials for the study include the Agreement on cooperation of the CIS member States in the fight against crimes in the field of computer information of June 1, 2001, the Agreement on cooperation of the CIS member States in the fight against crimes in the field of information technology of September 28, 2018, as well as other international legal documents in this area. The paper uses comparative, comparative-historical and other scientific methods of research, general and particular ones.RESEARCH RESULTS. The result of the study is a general assessment of the state of the international legal framework for the interaction of countries in the detection, investigation and prevention of crimes in the information and telecommunication sector, as well as an analysis of the part of it that has legal force for the Russian Federation. The structure, problems and directions of development of international legal regulation in this area are revealed.DISCUSSION AND CONCLUSIONS. Based on the problematic analysis of the current experience of international legal regulation of cooperation in the fight against crimes committed using information and telecommunication networks and in the field of computer information, the authors concluded that the existing international legal framework for such cooperation is insuffi ent and needs to be improved both at the universal and regional level.